BARRIERS TO COMPLETING CANCER TREATMENT PROTOCOLS FOR OLDER LATINOS. (11th November 2018) - Ring, L; Glicksman, A; Schwartz, A J
Abstract: This presentation will focus on a study designed to identify barriers to completing cancer treatment protocols among older Latinos living in Philadelphia. Radiation and chemotherapy treatments for cancer often require patients to adhere to complex treatment schedules which can be difficult for older adults to follow, especially those in low income and minority communities. In addition to experiencing high levels of poverty, a large proportion of Philadelphia's Latino population is non-English speaking and resides in geographically segregated neighborhoods. Older Latinos in these communities, even those that have adequate medical insurance, often face linguistic, cultural, and economic barriers to treatment adherence. This study seeks to better understand those challenges by conducting focus groups with several groups of key stakeholders – older adults, their caregivers, health care providers, and providers of social services. Our presentation will focus on prominent themes which emerged from these discussions, such as a lack of reliable transportation.